TAXA DE CRESCIMENTO DE MUDAS DE CAFEEIRO SOB APLICAÇÃO DE VITAMINA B3 - Meira, Leonardo Borges Vasconcelos; Souza, Maria Ingrid; VENDRUSCOLO, Eduardo Pradi; Lima, Sebastião Ferreira; Sant’ Ana, Gabriela Rodrigues (ANAIS DO ENIC, 2024)
-